Conjugated Polyelectrolyte Blend as Photonic Probe of Biomembrane Organization. Issue 14 (14th September 2016) - Zeglio, Erica; Schmidt, Martina M.; Thelakkat, Mukundan; Gabrielsson, Roger; Solin, Niclas; Inganäs, Olle
Abstract: In the following report, a conjugated polyelectrolyte (CPE) blend has been introduced for the first time as a fluorescent probe of membrane organization. Insertion of the blend into the lipid double layer has been rendered possible through formation of a hydrophobic complex by counterion exchange. Changes in membrane physical state from liquid‐disordered (Ldis ) to liquid‐ordered (Lord ), and to solid‐ordered (Sord ) result in red shifts of blend excitation (up to Δλex =+90 nm) and emission (up to Δλnm =+37 nm) maxima attributable to backbone planarization of CPEs. We found that blend stoichiometry can be adjusted to attain the best interplay among single polyelectrolytes properties, such as sensitivity and luminescence. The resulting probes therefore allow a bimodal detection of membrane physical state: changes in absorption permit a direct visualization of membrane organization, while variations in emission spectra demonstrate that CPE‐blends are a promising probes that can be used for imaging applications. Abstract : See the membrane. The photophysical properties of conjugated polyelectrolyte blends have been exploited as a tool for the development of hydrophobic probes for real‐time monitoring of biomembrane organization. Wavelength shifts of the probes in both excitation and emission provide with an immediate visualization of changes in membranes state as well as a quantitative information about the transition.